Analysis of population‐based colorectal cancer screening in Guangzhou, 2011‐2015. (29th March 2019) - Zhiqiang, Feng; Jie, Cao; Yuqiang, Nie; Chenghua, Gong; Hong, Wang; Zheng, Sun; Wanglin, Li; Yongjian, Zhou; Liping, Dai; Lizhong, Zeng; DeJian, Zhao
Abstract: Objective: To analyze the detection rates of colorectal cancer (CRC) and polyps by population‐based screening in Guangzhou. Methods: From January 2011 to December 2015, the residents aged 30‐79 were selected for CRC screening. The residents were conducted Questionnaires and/or FOBT to assess high‐risk groups, the free colonoscopy examination was recommended, and the results were evaluated in detail. Results: There were 98 927 residents involving screening, 5306 high‐risk residents identified (males 1859 and females 3447), and 4713 subjects underwent colonoscopy (males 1690 and females 3023). CRC was seen in 55 individuals (males 28 and females 27), and the detection rates in male were higher than in female ( P  = 0.019). And the detection rates increasing with age, for people over 60 years old, were obviously higher than those younger ( x 2  = 18.64, P  = 0.000924). The polyps were seen in 1458 (30.94%) cases， and 1420 subjects received pathological examination (adenomas 971 and non‐adenomatous polyps 449). Advanced adenomas were seen in 462 cases (males 240 and females 222) and 509 cases of non‐advanced adenomas (males 255 and females 254). For advanced adenomas, the detection rates in male were higher than female (14.20% vs 7.34%, P  = 2.64 × 10 −14 ). For the detection rates of adenomas or advanced adenomas by age, the people over 40 years were higher than younger (20.91% vs 3.61% P  = 7.87 × 10 −6 ; 9.94% vs 2.41%, P  = 0.009). Conclusions: For Guangzhou residents, the detection rates of CRC and adenoma were 1.17% and 20.60%. The detection rates of CRC increasing with age, for people over 60 years old, were obviously higher than those younger. But for people over 40 years, the detection rate of adenoma and advanced adenoma was higher than younger. So for people over 40 years, the CRC screening is recommended. Abstract : There were 98 927 residents involving screening and 4713 subjects (males 1690 and females 3023) underwent colonoscopy. CRC were seen in 55 individuals (male 28, female 27), and the detection rate in male were higher than in female (28/1690, 1.66% vs 0.89%, 27/3023, P = 0.019). And the adenomas were seen in 971 cases. Advanced adenomas were seen in 462 cases (male 240, female 222) and 509 cases of non‐advanced adenomas (male 255, female 254). For advanced adenomas, the detection rates in male were higher than female (14.20% vs 7.34%, P = 2.64 × 10 −14 ). For the detection rates of adenomas or advanced adenomas by age, the people over 40 years were higher than younger (20.91% vs 3.61%, P = 7.87 × 10 −6 ; 9.94% vs 2.41%, P = 0.009).